The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1002/aenm.201700683
|View full text |Cite
|
Sign up to set email alerts
|

4‐Tert‐butylpyridine Free Organic Hole Transporting Materials for Stable and Efficient Planar Perovskite Solar Cells

Abstract: 4‐Tert‐butylpyridine (tBP) is an important additive in triarylamine‐based organic hole‐transporting materials (HTMs) for improving the efficiency and steady‐state performance of perovskite solar cells (PVSCs). However, the low boiling point of tBP (196 °C) significantly affects the long‐term stability and device performance of PVSCs. Herein, the design and synthesis of a series of covalently linked Spiro[fluorene‐9,9′‐xanthene] (SFX)‐based organic HTMs and pyridine derivatives to realize efficient and stable p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
87
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(89 citation statements)
references
References 49 publications
0
87
0
2
Order By: Relevance
“…proposed that the donor‐π‐donor planar structure could be strategically important to design small‐molecule HTMs on account of improving charge transfer property and efficient charge extraction properties at the interface between perovskite and HTM . The results from Jen and co‐workers exhibited that pyridine‐functionalized HTM has a vital role in increasing the stability of PSCs . Just recently, our group further studied the variation tendencies of energy level and hole transport property with the change of position and number of methoxy groups for spiro‐CPDT.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…proposed that the donor‐π‐donor planar structure could be strategically important to design small‐molecule HTMs on account of improving charge transfer property and efficient charge extraction properties at the interface between perovskite and HTM . The results from Jen and co‐workers exhibited that pyridine‐functionalized HTM has a vital role in increasing the stability of PSCs . Just recently, our group further studied the variation tendencies of energy level and hole transport property with the change of position and number of methoxy groups for spiro‐CPDT.…”
Section: Introductionmentioning
confidence: 99%
“…[7] The resultsf rom Jen and coworkers exhibited that pyridine-functionalized HTM has av ital role in increasing the stability of PSCs. [8] Just recently,o ur group further studied the variation tendencies of energy level and hole transport property with the change of position and number of methoxy groups fors piro-CPDT.R esults showed that meta-substitution benefits reducing of the highest occupied molecular orbital( HOMO) levels, and ortho-substitutiono r mixed ortho-and para-substitution could increaset he hole mobility. [9] We also investigated the influence of conjugate unit length on energy level and hole mobility,a nd we found that when the number of conjugate thiophtheneu nit is more than 4, the HOMO level is ac onstant,a nd molecule size ando dd or even number of thiophtheneu nit co-influence the hole transfer property.…”
Section: Introductionmentioning
confidence: 99%
“…First, the key fluorine containing core moiety 2,7‐dibromo‐3′,6′‐difluoro‐spiro(fluorene‐9,9′‐xanthene) (2Br2F‐SFX) was prepared via one‐pot cyclization reaction of the commercial available 2,7‐dibromo‐9‐fluorenone and 3‐fluorophenol using methanesulfonic acid as catalyst . Subsequently, Buchwald‐Hartwig amination of the 2Br2F‐SFX and 4,4′‐dimethoxydiphenylamine in the presence of palladium‐catalysts afforded the target compound 2 m F‐X59 . The detailed synthetic information and full chemical characterization of the intermediate and target product were fully accessible in the Supporting Information.…”
Section: Resultsmentioning
confidence: 99%
“…The SFX‐terminated X59 , which is called X55 , achieved a high efficiency of 20.8% with high T g (174.4 °C) and hole mobility (6.81 × 10 −4 cm 2 V −1 s −1 ) (Figure ) . A tBP‐free HTM, called XPP , was developed to achieve 19.5% of efficiency in the PerSC (Figures d and ) . XPP was designed with two para ‐substituted pyridines on the SFX core unit to perform the role of a tBP without the liquid‐type tBP as a dopant.…”
Section: Htms In Conventional Structures (N–i–p)mentioning
confidence: 99%